Age Differences in the Interpretation of Facial Emojis: Classification on the Arousal-Valence Space - Kutsuzawa, Gaku; Umemura, Hiroyuki; Eto, Koichiro; Kobayashi, Yoshiyuki (Frontiers in Psychology, 2022)
Emojis are a universal tool frequently used for expressing one's emotional state in daily communication. Additionally, they are often applied in research fields, such as consumer surveys, as an indicator for assessing a user's emotional state. Thus, to ensure the validity of using emojis as a metric for such studies and reduce misunderstandings, further analyses of emoji interpretation across demographics (age, gender, culture, etc.) are necessary. However, details regarding the effect of age on both arousal and valence in the interpretation of emojis remain unclear. Therefore, this study aims to understand the interpretation of facial emojis on the arousal-valence space among various age groups. In an online survey involving 2,000 participants, a nine-point scale was employed to evaluate the valence and arousal levels of 74 facial emojis. The results revealed the following points: 1) emojis are categorized into six similar clusters on the two axes of values and arousal for both age groups, 2) the middle-aged group tends to indicate significantly higher arousal levels than the young group for two negative clusters (i.e., a strongly and moderately negative sentiment), and 3) not all emojis classified into these two negative clusters indicate an age difference. Based on the results, the study suggests using emojis with no age effect for the negative clusters as indices for measuring human emotions.